IbM DAUR ULANG SAMPAH DI PALEBON - Sri Rejeki Retnaningdyastuti; Venty Venty; Donny Anhar Fahmi (Journal of Dedicators Community, 2017)
Garbage is defined as a material/ remnant of unwanted things after a final use process. A large number of the garbage heaps which cannot be overcome will cause many problems both directly and indirectly to inhabitants and surroundings. According to the survey, there is a garbage dump near people’s settlement. It makes an unhealthy environment and disturbs people’s health surroundings because of the inappropriate garbage heap, so that the existence of garbage is very fidgety to people. Such a condition causes garbage disposal to become the most difficult problem in Palebon district, Pedurungan subdistrict which should be handled soon. Solutions which are offered focus on the additional infrastructure especially sets of production equipment (compost cultivation container), organic compost production and non-organic garbage utilization into people’s work RW I and RW II which can be implemented well, effective and efficient marketing process, and PKK (home economic) that will be founded to manage non-organic garbage into beneficial handicrafts. Based on the garbage-recycling activity devoted to people, the team has successfully made a compost cultivation container, work of non-organic garbage, as well as garbage cultivation marketing training.  Keywords: technology, recycling, garbage